Bacterivorous Nematodes Drive Ammonification and Bacterial Community Growth in a Strongly Acidic Soil - Shuo Na; Helen L. Hayden; Ji‐Zheng He; Zi‐Yang He; Reza Ghaderi; Li Bi; Hang‐Wei Hu (Journal of Sustainable Agriculture and Environment)
ABSTRACT Nematodes, the most abundant animals on Earth, play a vital role in the soil biosphere by regulating microbial communities and influencing nutrient cycling. However, their grazing impact on soil nitrogen (N) cycling and microbial communities remains insufficiently understood. In this study, we addressed this knowledge gap through a microcosm experiment using gamma‐sterilised acidic soil (pH < 4.5), inoculated with either microbial suspension alone or in combination with low or high concentrations of nematodes. Our results revealed that nematodes significantly increased soil NH₄⁺–N content and bacterial abundance, with bacterivorous nematodes increasingly dominating the microcosm environment. This study provides new evidence that bacterivorous nematodes significantly enhance ammonification in acidic soil, with implications for soil N availability and agricultural productivity.